Impact of Coronavirus Disease 2019 on the Diagnosis and Treatment of Pancreatic Cancer: An Observational Cohort Study - Chon, Hyung Ku; Lee, Eun Jee; Lee, Yun Chae; Kim, Seong-Hun (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Early pancreatic cancer diagnosis is crucial for timely intervention and better outcomes. The coronavirus disease 2019 (COVID-19) pandemic has disrupted routine health care globally. The COVID-19 pandemic has disrupted routine health care globally. This study aimed to evaluate the impact of COVID-19 on the diagnosis and treatment of pancreatic cancer. Materials and Methods: This retrospective study compared pancreatic cancer patients from 2 tertiary hospitals in pre and COVID-19 periods. Pre-COVID-19 period spanned from January 1, 2018, to January 19, 2020, while the COVID-19 period extended from January 20, 2020, to December 31, 2021. Results: A total of 542 patients were included. In the pre-COVID-19 period, 280 new cases of pancreatic cancer were enrolled, compared to 262 during COVID-19. The annual incidence rates were 136.63 and 134.50 patients, respectively. The median age was significantly lower during COVID-19 (71.5 years) compared to pre-COVID-19 (77 years) (P < .001). In subgroup analyses for stage 3 and 4, the proportion of stage 4 pancreatic cancer increased during COVID-19 (χ2 = 5.53, P = .019), and the COVID-19 group had younger diagnoses, better performance status, more surgery, higher use of FOLFIRINOX chemotherapy, fewer hospital referrals, and better median overall survival compared to the pre-COVID-19 group. Conclusion: This study revealed changes in the characteristics and treatment of patients diagnosed with pancreatic cancer during the COVID-19 pandemic. Although further large-scale research is necessary, the findings of this study can function as foundational data for formulating policies for the management of patients with pancreatic cancer during future pandemics of other infectious diseases. Cite this article as: Chon HK, Lee EJ, Lee YC, Kim S. Impact of coronavirus disease 2019 on the diagnosis and treatment of pancreatic cancer: An observational cohort study. Turk J Gastroenterol. 2024;35(5):408-417